INOVASI BAHAN AJAR ARITMATIKA SOSIAL BERLANDASKAN PROBLEM SOLVING PADA KELAS VII - Suharti Suharti; Sri Nensi Roslan; Mardhiah Mardhiah; Fitriani Nur (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The type of research used is Research and Development with reference to the Plomp development model which consists of several phases, namely the preliminary investigation phase, the design phase, the realization phase and the test, evaluation and evaluation phase.  revision (Test, Evaluation and Revision).  The product developed in the form of teaching materials, namely problem solving based modules on social arithmetic material, the test subjects in this study were class VIIB students of SMPN 19 Bulukumba with 30 students.  The instruments used in this study were expert validation sheets, student activity observation sheets, teacher ability observation sheets in managing learning, student response questionnaires, teacher response questionnaires, and learning outcomes tests.  Based on the results of the limited trials carried out, it was found that (1) the results of the validation of teaching materials were 4.4 in the "Sangan Valid" category because they were in the interval 4.3 M 5, (2) practical because the average percentage for student responses was  89.2% and the average percentage for teacher responses was 92.5%, each in the “Very Positive” category.  (3) effective so that it can meet three criteria, namely the average ability of teachers in managing learning is 4.67 in the "Very Good" category, the average percentage of student activity is 73.2% in the "good" category and the percentage of completeness  student learning is in the "high" category and achieve classical completeness, namely 83.3% of students classically complete.  So it can be concluded that in the limited trials carried out, problem solving based modules on social arithmetic material in class VII SMPN 19 Bulukumba have met the criteria of validity, practicality and effectiveness.